Effectiveness of Giving Muntingia Calabura Leaves and Muntingia Calabura Fruit (Muntingia Calabura L) on Blood Sugar Levels In Type 2 Diabetes Mellitus Patients: Literature Review - Konita Shafira; Abu Bakar; Erna Dwi Wahyuni (Universitas Airlangga, 2021)
Introduction : Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia caused by abnormalities in insulin secretion, thus impacting on blood glucose levels. Calabura muntingia leaves are traditionally used as an alternative medicine because they contain flavonoid compounds which have anti-diabetic properties. In general, it is known that how to make traditional medicine is by boiling it, where the solvent only uses water so that the polar compounds will be attracted. The purpose of this study is to explain effectiveness the effect of administration between calabura muntingia leaves and calabura muntingia fruit through a review of studies related to blood sugar levelsin the last ten years.Method : Search for journals or articles using Scopus, Proquest, and Scholar indexed databases using appropriate keywords. The Center for Review and Dissemination and The Joanna Briggs Institute was used to assess the quality of the study. The framework used for the review is PICOS and the inclusion criteria used are English and Indonesian journals published in 2010 to 2020. Data analysis and tabulation are carried out in articles or journals. Title, abstract, full text and methodology are assessed to determine the eligibility of the article or journal.Results : Six hundred and forty-one articles were identified, there were eleven articles that fit the research criteria. The leaves of muntingia calabura and fruit of muntingia calabura contain flavonoids and saponins which can reduce blood sugar levels. A flavonoid compound that is thought to have activity in reducing blood glucose levels is quercetin.Conclusion : The form of extract, infusion, juice and stew did not change the content of the calabura muntingia plant.